1931
DOI: 10.1001/jama.1931.02720460010003
|View full text |Cite
|
Sign up to set email alerts
|

Nervous Symptoms as Earliest Manifestations of Carcinoma of the Pancreas

Abstract: of toxemia, twice during difficult versions in primiparous patients, and three times of unknown causes. Diagnosis of cerebral hemorrhage was made eight times : four times clinically and four times by autopsy observations. Of these eight cases, five occurred among patients in whom the second stage was prolonged over

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0
3

Year Published

1931
1931
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(40 citation statements)
references
References 3 publications
2
35
0
3
Order By: Relevance
“…In 1931, depression, anxiety, insomnia, and weight loss were described for the first time as earliest manifestations of pancreatic cancer [22]. Later, several studies confirmed depression as a prodrome of this disease [23,24,25,26].…”
Section: Resultsmentioning
confidence: 99%
“…In 1931, depression, anxiety, insomnia, and weight loss were described for the first time as earliest manifestations of pancreatic cancer [22]. Later, several studies confirmed depression as a prodrome of this disease [23,24,25,26].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, reporting high incidence rates for Pancreatic cancer is still one of the malignancies with the worst prognosis and associated with a high prevalence of depression. This relationship was already described about 70 years ago, but is still poorly understood [1,2] . Dealing with this subject, one pivotal question remains: is this depression a feature of pancreatic cancer per se or is it rather a response to the experience of gradual loss of strength and body weight in patients with a life-threatening diagnosis?…”
mentioning
confidence: 93%
“…After the initial description in 1931, several studies have reported on the association between pancreatic cancer and the triad of anxiety, depression and 'sense of impending doom' [1,2,4,5] . Remarkably high incidence rates were affirmed by a study in 1993 which showed depressive symptoms in 71% of the explored pancreatic cancer patients and 'anxiety-related symptoms' in 48% of the patients [6] .…”
mentioning
confidence: 99%
“…Long before the advent of psychotropic medications, Yaskin 4 in 1931 reported that clinical depression may be the earliest manifestation of a pancreatic carcinoma. Later work demonstrated that pancreatic cancer is the entity with the highest incidence of depression among all tumors of the digestive system.…”
mentioning
confidence: 99%